Evaluation of Recombinant Herpes Zoster Vaccine for Primary Immunization of Varicella-seronegative Transplant Recipients. Issue 10 (October 2021) - L'Huillier, Arnaud G.; Hirzel, Cedric; Ferreira, Victor H.; Ierullo, Matthew; Ku, Terrance; Selzner, Nazia; Schiff, Jeffrey; Juvet, Stephen; Miao, Congrong; Schmid, D. Scott; Humar, Atul; Kumar, Deepali
Abstract : Background: Immunization of varicella-zoster virus (VZV)-seronegative solid organ transplant (SOT) patients using the live-attenuated varicella vaccine is generally contraindicated, leaving no widely applicable immunization option. The recombinant subunit herpes zoster vaccine (RZV) is indicated for VZV-seropositive persons to prevent shingles but could potentially also protect VZV-seronegative persons against varicella. We performed a safety and immunogenicity evaluation of RZV in VZV-seronegative SOT recipients as an option for protection. Methods: VZV-seronegative adult SOT patients with no history of varicella/shingles vaccine or disease were given 2 doses of RZV vaccine 2–6 mo apart. Blood was drawn prevaccination (V1), before the second dose (V2), and 4 wk after the second dose (V3). Humoral immunity (anti-glycoprotein E) and cell-mediated immunity were evaluated, with polyfunctional cells defined as cells producing ≥2 cytokines. Results: Among 31 eligible VZV-seronegative SOT patients screened, 23 were enrolled. Median age was 38 y and median time since transplant procedure was 3.8 y. The most frequent transplant types were liver (35%) and lung (30%). Median anti-glycoprotein E levels significantly increased from V1 to V3 ( P = 0.001) and V2 to V3 ( P < 0.001), even though only 55% had a positive seroresponse. Median polyfunctional CD4 T-cell counts increased from V1 to V2 (54/10 6 versus 104/10 6 cells; P = 0.041) and from V2 to V3 (380/10 6 ; P = 0.002). Most adverse events were mild with no rejection episodes. Conclusions: RZV was safe and elicited significant humoral and cellular responses in VZV-seronegative SOT patients and has the potential to be considered as a preventive strategy against primary varicella. Abstract : Supplemental Digital Content is available in the text.